Perceptions of Border Area Lecturers and Students Regarding the Use of Computer Technology and Smartphone Applications in Learning English - Woro Kusmaryani (Universitas Pendidikan Mandalika, 2021)
This study aimed at exploring the use of computer technology and smartphone applications in the learning of English. A case study design using questionnaires and interview data was expected to reveal lecturers and students' perceptions comprehensively. The data obtained were analyzed with quantitative and qualitative data analysis in descriptive statistics and coding. This study indicated that computer technology and smartphone applications in learning English could smoothly run if the internet network was stable and there was a sufficient data quota. In its use, both lecturers and students needed to coordinate well regarding the English learning platform used. Both lecturers and students needed to prepare, implement structured learning, and pay attention to learning evaluation.